Information and Communication Technologies in Tourism 2021 2021
DOI: 10.1007/978-3-030-65785-7_54
|View full text |Cite
|
Sign up to set email alerts
|

Examining Post COVID-19 Tourist Concerns Using Sentiment Analysis and Topic Modeling

Abstract: The COVID-19 pandemic has had a destructive effect on the tourism sector, especially on tourists’ fears and risk perceptions, and is likely to have a lasting impact on their intention to travel. Governments and businesses worldwide looking to revive and revamp their tourism sector, therefore, must first develop a critical understanding of tourist concerns starting from the dreaming/planning phase to booking, travel, stay, and experiencing. This formed the motivation of this study, which empirically examines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The study shows how the destination's image is related to the spatiality within the destination and the visitor's emotional response. Similar recent studies are such as Gulati [58] shedding light on "vaccine tourism" through public sentiments and emotions based on Twitter's data; Balasubramanian et al [59] examining post-COVID-19 tourist concerns; and Park et al [60] identifying predominant topics and associated emotions about European and Asian destinations during the COVID-19 pandemic.…”
Section: Sentiment Analysis In Tourism Researchmentioning
confidence: 69%
“…The study shows how the destination's image is related to the spatiality within the destination and the visitor's emotional response. Similar recent studies are such as Gulati [58] shedding light on "vaccine tourism" through public sentiments and emotions based on Twitter's data; Balasubramanian et al [59] examining post-COVID-19 tourist concerns; and Park et al [60] identifying predominant topics and associated emotions about European and Asian destinations during the COVID-19 pandemic.…”
Section: Sentiment Analysis In Tourism Researchmentioning
confidence: 69%
“…Furthermore, our findings are consistent with the work of Sun et al (2021), which showed that awe and worry are positively correlated with environmentally conscious behavior, and that awe predicted worry. This serial mediation model revealed that multiple emotions contribute to responsible consumption (Balasubramanian et al , 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The pandemic has had a disparaging influence on the travel and tourism sector, specifically on travelers' anxieties and risk perceptions, and it has a longlasting negative effect on their intention to travel. Currently, the globe is working to revitalize and modernize the tourist sector, especially those nations that depend on travel and tourism-related earnings (Balasubramanian et al, 2021). Women's entrepreneurial behavior is a possible source of reviving the business and a competitive advantage (Bhandari & Amponstira, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies about the relationship of EO and performance of tourism industry (I. Ocheni et al, 2020;Tang et al, 2020;Balasubramanian et al, 2021;Luu, 2021) as well as the mediating effect of competitive advantage on them (Kiyabo & Isaga, 2020; Mostafiz, Hughes, & Sambasivan, 2021). However, the studies related to women entrepreneur on the tourism industry are limited (Ribeiro et al, 2021;Filimonau et al, 2022).…”
Section: Introductionmentioning
confidence: 99%